नेपालको संविधान निर्माण प्रक्रियामा जनसहभागितामूलक लोकतन्त्रको अभ्यास - Pulami, Mohan Lal (Haimaprabha, 2025)
The present article has been prepared with the objective of studying democratic public participation in the constitution-making process of Nepal. An attempt has been made to measure the democratic system on the basis of the public participation principle in the constitution-making process on the basis of the concepts and values ​​mentioned in the preambles of the constitutions. A qualitative framework is used for document analysis and a purposeful sample method has been adopted. In this article, the participatory principle mentioned in the preamble of the constitution has been made the theoretical basis. Although the state system has been operating on the basis of culture and convention, the background of constitutional development begins from 2004 BS. Seven constitutional documents have come into existence in Nepal so far and other constitutions have been implemented except for the ‘Government of Nepal Act, 2004’. While studying the nature of the construction of those constitutions, a preamble has been included in all of them. However, it has been concluded that the 'Constitution of Nepal, 2072' drafted by the Constituent Assembly has a more liberal democratic character than the constitution drafted by the Constitution Commission formed by the king.